Current state of female leadership in higher education institutions in Saudi Arabia - Dina Abdullah Dahlan (Cogent Business & Management, 2023)
In Saudi Arabia's higher education, women remain an untapped resource, with many limitations in holding key positions and pursuing professional career development. However, over the past few years, the government of Saudi Arabia has actively promoted female leadership by implementing Vision 2030. Considering the substantial progress made in female leadership, it is imperative to explore the present state of female leadership in higher education institutions in the country. Additionally, there is a general scarcity of research on the role of women in Saudi higher education. Semi-structured interviews were conducted with 23 academic professionals. The data were analyzed following a thematic approach using NVivo 12 software. The results indicated that the acceptance of female leaders in Saudi Arabia's higher education sector is highly subjective and depends on several factors (e.g. age, educational background, and leader's proficiency). Despite the perceived need to diversify the system and use females' potential capabilities to advance education, the participation of females in leadership positions still lags behind that of males. Based on our thematic analysis results, there is currently no specific process for identifying and selecting new leaders, and future leaders are mainly chosen by top powers in the university. Although the Saudi government strongly supports female leadership through Vision 2030, it is occurring at a slow pace. The findings of this study contribute to the body of knowledge by prompting the government and decision-makers to consider taking actions that would foster females' talent, and consequently, the integration of more women into the educational system
Keywords: 650; female leadership; higher education; Saudi Arabia; Vision 2030